Guidance And Counseling Management In Overcoming Bullying Problems For Students - Shelvia Eka Septiana; Nur ‘Azah (International Journal of Interdisciplinary Research, 2026)
This study aims to examine how guidance and counseling management is implemented, how bullying problems occur, and how the role of guidance and counseling management in overcoming bullying in students. This research uses a qualitative approach with a case study type. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation of sources, time, and techniques. The results showed that (1) guidance and counseling management is carried out systematically through planning, implementation, evaluation, and follow-up, involving all elements of the school. (2) The problem of bullying, whether verbal, physical, or relational, is still a challenge and has a negative impact on students. (3) Guidance and counseling management overcomes bullying through innovative programs such as the caring task force team, Friday confide, laposi, roleplayers, and social emotional training, fully supported by the school. These programs successfully create a safe space and increase student awareness. It is recommended that these programs continue to be developed and socialized more widely.